Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This expression: $x(t)=[e^{-3t+5}] u(t-1)$.

I am trying to take the Fourier transformation of the above expression.

I know that for $x(t)=[e^{-at}] u(t) \leftrightarrow \frac1{i\omega+a}$.

But, how am I supposed to transform the above expression? It looks similar to the known transformation, but it certainly is not =/

Thanks!

share|improve this question

2 Answers 2

up vote 0 down vote accepted

Write $x(t) = e^{-3t+5}u(t-1) = e^{-3t+3+2}u(t-1) = e^2\cdot e^{-3(t-1)}u(t-1)$.

Now notice that $x(t)$ is a shifted version of $y(t) = e^2 \cdot e^{-3t}u(t)$, so apply the shift theorem to $y(t)$ and you should have your result.

share|improve this answer

$x(t)=[e^{-3t+5}] u(t-1)=[e^{-3(t-1)+2}] u(t-1)=e^2 e^{-3\tau}u(\tau), $ where $\tau=t-1.$ Then use linearity of Fourier transform.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.